Boosting Malaysian Tourism – The Food Way! - Zulaika Zakariah; Ratna Khuzaimah Mohamad; Wardah Mohamad (International Association of Computer Science & Information Technology Press, 2012)
Malaysia‟s aim to become a developed nation has spurred growth in many areas of the economy including tourism. Malaysian tourism destinations have been well promoted along with the uniqueness of the Malaysian culture which is an exciting blend of the Malay, Chinese, Indian and other native subcultures. However, one of the reasons tourists repeatedly come back to the country has been neglected. This paper focuses on this – how food can be used as a strategy to boost Malaysian tourism. A comparative study is done on how Hong Kong and Singapore has capitalized on food in their tourism initiatives. Based on this, a comparison is then made on what has been done in Malaysia and what is still missing. Five key strategies are proposed to boost Malaysian tourism including food trails, on-line promotions, quality certification, culinary classes and packages and community involvement. These will contribute to the number of tourist arrivals, regional development, tourist pattern of dispersion and community development. (Abstract by authors)